MERAWAT KALI-MERANCANG ASA KOTA KONTESTASI DAN PARTISIPASI KOMUNITAS ATAS DINAMIKA SUNGAI DI KOTA SURAKARTA - Siti Zunariyah; Akhmad Ramdhon (Jurnal Sosiologi Reflektif, 2017)
These cities are change by the development scheme compelled by various economic, politic and cultural interests in central and local relations. In the last decades, the dominant condition of physical aspect-oriented development does not change as well. In some aspects, the scale is getting larger and more massive with decentralization interest. The delegated authority in policy framework gives the local government the foundation of accelerating the change through some autonomous scheme, in which the most dominant orientation among all of those attempts is the city transforming with economic-political reasoning. On the other hand, decentralization also gives the citizens the opportunity of being the part of transformation scheme designed by government. Participation Space allows for the involvement in various policies that will be undertaken in collective contestation in public domain.  This article narrates how the urban development scale changes the urban spaces and impacts on the urban ecology, namely river. Narration of river transformation in the last decade is that the river transforms due to many factors and it can be seen from both physical and non-physical transformation. The existing development orientation marginalizes the river and at the same time river assumes the development burden. The crucial point of participation idea is inseparable as well from the relationship between city, river, and citizens staying living in urban kampong daily. The growing response of community is interesting to be studied as the part of understanding the urban physical transformation on the one hand and citizen’s social dynamics on the other hand. Decribing Surakarta and Cities provides the construction of community interest relation complexity and the reinterpretation of river as the part of city. The dynamics of urban kampong in river area can represent the contestation of values, interests and social relations in urban context.  Keyword: City, Kampong, River, Community, Participation